Chitin-degrading enzymes from an actinomycete ectosymbiont of Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) - Rossi, Guilherme Duarte [UNESP]; Zucchi, Tiago Domingues; Guidolin, Aline Sartori; Peruchi, Aline; Cônsoli, Fernando Luis (Springer, 2015)
Microbes have many mechanisms to exert their inhibitory activity against target pests. One such mechanism involves the production and secretion of hydrolytic enzymes, such as chitinases, which are produced naturally by plants in response to attack by insect herbivores and phytopathogens and have been sought as an additional factor to enhance pest management. Thus, our main aim was to screen the diverse actinomycete community associated with the integument of Acromyrmex subterraneus brunneus for a chitinase-producing strain and to characterize its chitinases. We identified isolate ENT-21-a Streptomyces sp.-as a chitinase-producer and our data indicate that this isolate produces a chitinolytic complex that contains a chitinase and a high-molecular-weight beta-N-acetylglucosaminidase (> 100 kDa) when cultured in Chitin-Czapek broth. The presence of chitinases in the genome of this isolate was checked by diagnostic PCR, and two chitinase genes belonging to family 18 group A and family 19 were verified. The chitinolytic activity of the crude extract was observed at pH values ranging from 3.8 to 11.0, with the highest chitinase activities recorded at pH 9.0 and 9.5, whereas optimum beta-N-acetylglucosaminidase activity was observed over a narrow pH range, between pH 4.7 and 5.1. We describe some biochemical and molecular properties of the chitinase and beta-N-acetylglucosaminidase produced by ENT-21, and discuss the potential for exploitation of these enzymes for pest control.
Keywords: Streptomyces; Chitinases; Beta-N-acetylglucosaminidase; Biotechnology